Technique Of Free Full-Thickness Auto dermoplasty For Mammary Glands - Sardor U. Nazirov (Genius Journals, 2023)
The study is based on the results of surgical treatment in 46 female patients with postburn scar deformities of the soft tissues of the breast. According to the variations of scar deformity plastic surgery, all patients were divided into two groups. The main group included 24 patients in whom an improved method of full-thickness free skin grafting was applied, and the comparison group included 22 patients in whom the traditional method of free skin grafting with split-thickness autograft was used. The proposed method of full-thickness autodermoplasty aims to improve graft survival by ensuring its tight adherence and reducing the risk of graft contraction. The long-term results from the main group led to a reduction in the frequency of late complications from 33.3% to 8.3%, resulting in an improvement in the rate of favorable outcomes from 63.6% to 83.3%.
Keywords: Mammary glands; burn; consequences